Electrochemical degradation of surfactants in domestic wastewater using a DiaClean® cell equipped with a boron-doped diamond electrode - Cisneros-León, Dayana G.; Espinoza-Montero, Patricio J.; Bolaños-Mendez, Diego; Alvarez-Paguay, Jocelyne; Fernández, Lenys; Saavedra-Alulema, Pablo F.; Lopez, Kelly; Astorga, Diana; Piñeiros, José Luis (Frontiers in Chemistry, 2023)
Treating domestic wastewater has become more and more complicated due to the high content of different types of detergents. In this context, advanced electro-oxidation (AEO) has become a powerful tool for complex wastewater remediation. The electrochemical degradation of surfactants present in domestic wastewater was carried out using a DiaClean® cell in a recirculation system equipped with boron-doped diamond (BDD) as the anode and stainless steel as the cathode. The effect of recirculation flow (1.5, 4.0 and 7.0 L min−1) and the applied current density (j = 7, 14, 20, 30, 40, and 50 mA cm−2) was studied. The degradation was followed by the concentration of surfactants, chemical oxygen demand (COD), and turbidity. pH value, conductivity, temperature, sulfates, nitrates, phosphates, and chlorides were also evaluated. Toxicity assays were studied through evaluating Chlorella sp. performance at 0, 3, and 7 h of treatment. Finally, the mineralization was followed by total organic carbon (TOC) under optimal operating conditions. The results showed that applying j = 14 mA cm−2 and a flow rate of 1.5 L min−1 during 7 h of electrolysis were the best conditions for the efficient mineralization of wastewater, achieving the removal of 64.7% of surfactants, 48.7% of COD, 24.9% of turbidity, and 44.9% of mineralization analyzed by the removal of TOC. The toxicity assays showed that Chlorella microalgae were unable to grow in AEO-treated wastewater (cellular density: 0 × 104 cells ml−1 after 3- and 7-h treatments). Finally, the energy consumption was analyzed, and the operating cost of 1.40 USD m−3 was calculated. Therefore, this technology allows for the degradation of complex and stable molecules such as surfactants in real and complex wastewater, if toxicity is not taken into account.